PENGARUH KUALITAS PELAYANAN, FITUR PAYLATER, PROMOSI DAN KEMUDAHAN APLIKASI TERHADAP MINAT BELI ULANG PADA SHOPEE : (Studi kasus: Mahasiswa di Daerah Istimewa Yogyakarta) - Inri Yani; Sutarni Sutarni (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to test empirically the effect of service quality, paylater features, promotions and ease of application on repurchase intention. The population in this study were students using the Shopee marketplace in the Special Region of Yogyakarta. The sample of this research is Shopee user students who have bought on the Shopee marketplace more than once. The analytical method used is Moderated Regression Analysis (MRA). The technique of taking samples using purposive sampling. The results of this study indicate that service quality, paylater features, promotions and ease of application have a positive effect on repurchase intention. Quality of service, paylater features, promotions and ease of application have a joint effect on repurchase intention.